Asymptotic expressions for changes in the surface co-seismic strain on a homogeneous sphere. Issue 1 (9th January 2017) - Tang, He; Sun, Wenke
Summary: In the dislocation theory for a spherical Earth model, the computation of surface co-seismic deformations using straightforward numerical methods is time consuming and may encounter a series of convergence problems, especially for the near-field deformations due to shallow earthquakes. This study proposes an asymptotic method to approximate changes in the co-seismic surface strain that are caused by an arbitrary point dislocation in a homogeneous sphere. The corresponding expressions are in analytical form and can overcome these difficulties without the numerical integration of differential equations and summations of infinite associated Legendre series in practical applications. Importantly, in contrast with the classical solution for a half-space Earth model, the asymptotic solution can reflect the effect of the Earth's curvature.